1990
DOI: 10.1192/bjp.156.3.425
|View full text |Cite
|
Sign up to set email alerts
|

Single-Photon Emission Computerised Tomography (Spect) in Schizophrenia

Abstract: SPECT studies were carried out on three occasions in a woman with schizophrenia. Marked 'hypofrontality' was demonstrated during an acute phase of illness. A study during remission was within normal limits, but some return of the original defect was noted in a subsequent relapse. These findings parallel those found in PET studies of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The results obtained from these SPECT studies closely parallel those obtained from positron emission tomography (Holman, 1986;Hunter et al, 1989). In the realm of neuropsychiatric disorders, relatively little attention has been devoted to SPECT studies of affective illness and schizophrenia (Hawton et al, 1990;O'Connell et al, 1989).…”
supporting
confidence: 57%
See 2 more Smart Citations
“…The results obtained from these SPECT studies closely parallel those obtained from positron emission tomography (Holman, 1986;Hunter et al, 1989). In the realm of neuropsychiatric disorders, relatively little attention has been devoted to SPECT studies of affective illness and schizophrenia (Hawton et al, 1990;O'Connell et al, 1989).…”
supporting
confidence: 57%
“…The results obtained from these SPECT studies closely parallel those obtained from positron emission tomography (Holman, 1986;Hunter et al, 1989). In the realm of neuropsychiatric disorders, relatively little attention has been devoted to SPECT studies of affective illness and schizophrenia (Hawton et al, 1990;O'Connell et al, 1989).Major depressive illness is one of the most common mental health problems in the elderly. It affects about 2-3% of individuals above the age of 60 (Alexopoulos, 1988).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…As regards the stability of the brain scans Spence (42) demonstrated that hypofrontality is dynamic over time and accompanies improvement in positive symptomatology. Nonetheless, it seems that negative symptoms are more stable and persistent, and related to cognitive dependent hypofrontality (43, 44). We tried to reduce the effect of these confounding variables by using score activation which allowed us to define a sort of hypofrontality which is found in young, unmedicated and neuroleptic‐naive samples and remains invariable (16, 45, 46).…”
Section: Discussionmentioning
confidence: 99%
“…But since this functional hypo-frontality can be influenced by various clinical factors such as psychological conditions (18, 19) and antipsychotic treatment (20, 21), its clinical significance in the diagnosis of schizophrenia has not been well established. In addition, since most of the previous studies did not have control over the task performance, a question was raised that whether the results of these studies reflect only the reduced motivation in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%